2021
DOI: 10.3390/ijerph18094709
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Positive Parenting and Promoting Healthy Living through Family Cooking Classes

Abstract: Background: The family is an important setting in the promotion of child health. The parent–child relationship affects the social and health development of children, and children’s healthy behaviors are associated with positive parenting strategies. The parent–child relationship is bi-directional and the connection between parenting and child health is complex. However, few parenting interventions work with parents and children together, and more knowledge is needed on how to develop and implement intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…This is an important finding because early adoption of healthy eating patterns is recognized to have lifelong impacts [35]. Furthermore, time cooking together in food insecure homes, may also improve the mental health of family members through the strengthening of important relationships [36]. This is relevant because a recent systematic review concluded that food insecurity is associated with increased risk of depression and stress [37].…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding because early adoption of healthy eating patterns is recognized to have lifelong impacts [35]. Furthermore, time cooking together in food insecure homes, may also improve the mental health of family members through the strengthening of important relationships [36]. This is relevant because a recent systematic review concluded that food insecurity is associated with increased risk of depression and stress [37].…”
Section: Discussionmentioning
confidence: 99%
“…42 The process of developing and implementing cooking classes mobilises families and contributes knowledge on how to engage the home as a setting for health promotion. 43…”
Section: Project Family Cooking Classesmentioning
confidence: 99%
“…Evaluation and research have led to evidence-based guidelines and recommendations on best practice culinary interventions [ 5 , 6 ]. In addition, research in this field is demonstrating evidence of a wide range of positive impacts and outcomes from cooking classes, depending on the scope such as increased family cohesiveness [ 7 ] and improved household food budgeting [ 2 ].…”
Section: Introductionmentioning
confidence: 99%